US: A Narrative History. Volume 2, Since 1865 - Davidson, James West
For your classes in American History, McGraw-Hill introduces the latest in its acclaimed M Series. The M Series started with your students. McGraw-Hill conducted extensive market research to gain insight into students' studying and buying behavior. Students told us they wanted more portable texts with innovative visual appeal and content that is designed according to the way they learn. We also surveyed instructors, and they told us they wanted a way to engage their students without compromising on high quality content. U*S: A Narrative History tells the story of us, the American people, with all the visually engaging, personally involving material that your students demand. From a trusted author team, this innovative text provides instructors who normally choose either a big or brief book with scholarly, succinct, and conventionally organized core content; a highly readable and unified narrative that is continental in scope; and a magazine format that engages students and helps them connect with the nation's past. More current, more portable, more captivating, plus a rigorous and innovative research foundation adds up to: more learning. When you meet students where they are, you can take them where you want them to be.